PLANNING OF TAMIANG ROAD FLEXIBLE PAVEMENT BY PASS - Rajib Muammar Rajib; Iqbal Iqbal; Firdasari Firdasari (Jurnal Media Teknik Sipil Samudra, 2021)
The requirements of a road can provide a surface layer that is always flat, strong construction so as to ensure comfort and safety for service (road life) which is quite longand requires minimal maintenance in various circumstances. The increasing population growth, and the condition of the old roads that have been damaged, therefore the need for land transportation infrastructure will increase along with the increasing number of vehicles every year in Aceh Tamiang District. This situation makes the reason that the need for an appropriate and efficient method in road planning in order to obtain the best results and meet the elements of safety in road use, so it is necessary to plan the thickness of flexible pavement on the Tamiang By Pass road with a length of 5 km using the 2013 and 2017Road Pavement Design Manual Method and compare the two methods. The results of pavement thickness planning based on the 2013 Road Pavement Design Manual Method, obtained pavement layer thickness based on Alternative Design Chart 3A column FF9, namely AC-WC = 4 cm, AC-BC = 6 cm, AC-Base = 24.5 cm, LPA Class A = 15 cm , Class B LPA = 15 cm, Selected Embankment = 35 cm, and CBR of subgrade = 2.386%. The results of the pavement thickness planning based on the 2017 Road Pavement Design Manual Method, obtained the thickness of the pavement layer based on the Design Chart 3B column FF7, namely AC-WC = 4 cm, AC-BC = 6 cm, AC-Base = 18 cm, LPA Class A = 15 cm, LPA Class B = 15 cm, Selected Embankment = 35 cm, and CBR of subgrade = 2,399 %. Of the two methods compared and reviewed so that each manual for flexiblepavement design is produced.